2022
DOI: 10.1088/1758-5090/ac40ee
|View full text |Cite
|
Sign up to set email alerts
|

A thermogelling organic-inorganic hybrid hydrogel with excellent printability, shape fidelity and cytocompatibility for 3D bioprinting

Abstract: Alginates are the most commonly used bioink in biofabrication, but their rheological profiles makes it very challenging to perform real 3D printing. In this study, an advanced hybrid hydrogel ink was developed, a mixture of thermogelling diblock copolymer, alginate and clay i.e. Laponite XLG. The reversible thermogelling and shear thinning properties of the diblock copolymer in the ink system improves handling and 3D printability significantly. Various three-dimensional constructs, including suspended filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Biomaterials have been widely used in tissue regeneration. An ideal biomaterial possesses essential properties such as hierarchical architectures and ECM composition similar to native tissues [ 41 ]. Nanofibers have been widely used in regenerative engineering due to their feasibility in modification, more interactions with tissue environment as well as delivery of regenerative signals to the tissues [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterials have been widely used in tissue regeneration. An ideal biomaterial possesses essential properties such as hierarchical architectures and ECM composition similar to native tissues [ 41 ]. Nanofibers have been widely used in regenerative engineering due to their feasibility in modification, more interactions with tissue environment as well as delivery of regenerative signals to the tissues [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we used a commercially available bioink and a blend composed of alginate and POx, both showing the required features for printing [22,23]. The POx-Alginate bioink was included in this study to allow a head-to-head comparison with the commercial bioink.…”
Section: Discussionmentioning
confidence: 99%
“…The POx-Alginate bioink was included in this study to allow a head-to-head comparison with the commercial bioink. Previously, we have shown that the combination of alginate and the POx-based diblock copolymer hydrogels significantly improves the 3D printability of alginate and allows for long-term cell culture [23]. Now, we wanted to compare it directly with a commercial bioink to gauge the potential of our experimental bioink.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A process scheme showing the combination of 3D printing and cryostructuring is depicted in Figure 4. Regarding biological behavior, the CaMgP paste hardened by 3.5 M DAHP and the alginate used in this study have been separately evaluated in previous studies, [17,57] with positive results on cell viability. Thus, it is reasonable to assert that the dual component system here proposed is cytocompatible and promising for spine fusion and bone applications.…”
Section: Cryostructuring Process Evaluation and Combination With 3d P...mentioning
confidence: 99%